Exploring musician-educators' reflections on a collaborative cross-cultural music making encounter in Singapore. (August 2022) - Lim, Ernest Hung Choong; Yu, Georgette SY; Martin, Rose
Professional musician-educators from a tertiary arts institution in Singapore collaborated on a cross-cultural performance in Beijing as part of their professional development. Through a case study, semi-structured interviews explored the music making experiences of four of the musician-educators involved: the composer, the singer, the pianist and the erhu performer. Their experiences address the concept of cross-cultural music making and its significance in professional development for musician-educators. The experiences shared by the four musician-educators illuminate challenges, tensions and some areas to further resolve and critically question regarding how cultures are engaged in the process of music-making. Through unpacking the narratives of musician-educators and how they experience interactions with culture in music making, there is the possibility to further understand diverse music making encounters in Singapore.